Effects of self-selected or randomly selected music on performance and psychological responses during a sprint interval training session - Marques, M.; Staibano, V.; Franchini, E. (Science & Sports, 2022)
Objective The purpose of this study was to analyze the effects of self-selected and randomly selected music on perceptual and performance responses during a sprint interval training (SIT) session. Equipment and Methods 16 physically active males (M age = 27.0, SD = 3.9 years; M body mass = 78.1, SD = 9.6 kg; M height = 1.77, SD = 0.05 meters) performed a low-volume SIT session composed by 8 × 15s all-out bouts against a fixed load of 9% of body mass interspersed by 120s of passive recovery under three conditions: self-selected music (high-tempo subject's favorite music), randomly selected music (playlist from an online streaming music platform) and no-music. Affective responses, perceived exertion, and power output were measured throughout the protocols. Enjoyment and attentional focus were measured after the exercise sessions. Results Perceived exertion and affective responses did not differ between conditions; however, a main effect of time was detected for both variables, with perceived exertion increasing throughout protocols and affective responses decreasing (P < 0.001; for all comparisons). Attentional focus during recovery differed between conditions, with lower values in no-music (39 ± 26 a.u.) when compared to self-selected (65 ± 29 a.u.; P = 0.016) and randomly selected (63 ± 24 a.u.; P = 0.049). Power output measures did not differ between conditions, however, a main effect of time was observed for all measures (P < 0.001). Enjoyment was not affected by conditions and no interactions were detected for any of the measurements (P > 0.05 for all comparisons). Conclusion Music does not seem to promote effects on performance, perceived exertion, affective responses and enjoyment during an SIT session, however, listen to music during the recovery moments can improve the recovery status immediately before the next bout.